Tuning the photoluminescence of CdTe quantum dots by controllable coupling to plasmonic Au nanoparticles - Dzhagan, V.; Kapush, O.; Isaeva, O.; Budzulyak, S.; Magda, O.; Kogutyuk, P.; Trishchuk, L.; Yefanov , V.; Valakh, M.; Yukhymchuk, V. (Physics and Chemistry of Solid State, 2022)
A controllable variation of the photoluminescence (PL) intensity of semiconductor quantum dots (QDs) via their coupling to plasmonic nanoparticles (NPs) is the potential basis for optoelectronic and sensing applications. In this work, the effect of Au NPs on the PL of colloidal CdTe QDs is investigated in solution and solid films. An PL enhancement for the QDs synthesized in water was observed in case of spectral overlap of the plasmon absorption band of and QD PL band. In case of Au NPs synthesized in dimethyl sulfoxyl the trend is to reduction of the PL intensity. For the reference samples prepared by mixing QDs not with Au NP solutions but with corresponding pure solvent, certain PL enhancement was observed and presumably attributed to reduction of self-absorption or non-radiative interparticle interaction in less concentrated QD solution. However, the contribution of this dilution-related enhancement is expected to be independent of the spectral properties of NPs and QDs. Therefore, the observed in this work different behavior of QD PL in certain combinations of QDs and NPs is attributed to interaction between electronic excitation in the QD and plasmon.